First note of QTL mapping of low vigor traits using the updated F2 ‘Koroneiki’ linkage map of olive - Granata, Irene; Balan, Aparna S.; Di Vaio, Claudio; Ioppolo, Antonino; Caruso, Tiziano; Fretto, Silvia; Benny, Jubina; Giovino, Antonio; Sargent, Daniel James; Marra, Francesco Paolo; Marchese, Annalisa (Frontiers in Plant Science, 2025)
The olive tree (Olea europaea L.), which characterizes the agriculture of the Mediterranean basin, faces challenges adapting to high-density orchards and mechanized cultivation. This study addresses a key issue: controlling tree size to enhance efficiency and manageability in olive cultivation. Utilizing genetic mapping methods, we have identified significant Quantitative Trait Loci (QTL) and candidate genes associated with low-vigor traits in olive trees. Our research on the ‘Koroneiki’ F2 progeny, which exhibits low vigor traits but remains underutilized in breeding programs, has pinpointed a QTL linked to trunk basal diameter—a trait correlated with plant height based on morphological measurements. Results underscore a strong genetic control of these traits, with a consistent correlation observed over time. We identified two candidate genes — Acid Phosphatase 1, Shikimate O-hydroxycinnamoyltransferase, and a SNP Marker likely associated with Calcium Responsive Proteins — each potentially interacting with plant hormones to influence growth. Controlling olive tree size presents several challenges, including the genetic complexity of polygenic traits like size and vigor, and limited rootstock options. By integrating reference genomes with our genetic analysis, we offer a conceptual advancement that could substantially accelerate breeding timelines compared to traditional approaches. Although genome editing is still a future possibility due to the complexity of olive genetics and the species’ recalcitrance to transformation, our study lays a foundational understanding to guide future breeding programs. By targeting the identified candidate genes, this research represents a pivotal step toward selecting new low-vigor genotypes and rootstocks, contributing to innovations in olive cultivation.